Bābur aur us kā Hindūstān - ʻAbdurraḥmān, Ṣabāḥuddīn (Lāhaur : Prinṭ Lāʼin Pablisharz, 2001)
Biographical works on Babur, Emperor of Hindustan during 15th & 16th century.
Includes bibliographical references (p. [404]).
Mode of access: Internet.
In Urdu.
Keywords: Babur, -- Emperor of Hindustan, -- 1483-1530.; Mughal Empire -- Kings and rulers -- Biography; Mughal Empire -- History